Watch to Know: Short Films in LE/L2 Spanish Conversational Competence - Domènech, Conxita (2020)
This essay presents a second language (LE/L2) Spanish intermediate or advanced course based on short films, a genre overlooked both in the film industry and in the academia. Rather than a mere tool to amuse students a couple of times a semester, the short films will become the protagonists of the LE/L2 Spanish class. Although it might be categorized as a film or culture proposal, I have designed a conversational Spanish class. Like short films, conversation courses are underestimated and often labeled as easy. Therefore, this essay will examine neglected courses; put short films and conversation in their well-deserved place; and, above all, organize a LE/L2 conversation course based on short films. Before moving on to the proposal, I will briefly describe the intrinsic characteristics, recent history, and pedagogical benefits of the short films. I will continue with the presentation of the selected short films, providing basic information on each of them. I will conclude by choosing one of the short films and designing a pedagogical unit around it, which will serve as a model for the other short films.